The correlation of zinc serum levels and zinc intake with taste disorders in elderly patients at Babatan Public Health Center Bandung - Rahmatia Djou; Dewi Marhaeni Diah Herawati; Tenny Setiani Dewi (Faculty of Dentistry, Universitas Gadjah Mada, 2021)
Taste disorders, which can be caused by various factors, including deficiency of zinc levels in the body and lack of zinc, generally occur in the elderly. The aim of the study was to analyze the correlation between zinc serum levels and zinc intake, as well as the correlation between salivary volume, hypertension, and smoking with taste disorders in the elderly. This was analytical observational research with a cross-sectional method, which was conducted on 100 elderly patients, at Babatan Health Community Center, Bandung, Indonesia. The sampling was conducted through the following: interview about systemic disease history, drugs taken, and smoking habits; examination of oral cavity conditions; nutrition intake interviews; taste tests tests; and zinc serum measurement using the atomic absorption spectrometry. The data were obtained statistically. Among these one hundred elderly patients, 79 had low zinc serum levels and 94 had inadequate zinc intake. The average zinc serum in the elderly patients with taste disorders was 40.1 μg/dl, whereas those without taste disorders was 72.4 μg/dl, with a p value of <0.001. The average zinc intake in the elderly patients with taste disorders was 3.4, whereas in those without taste disorders was 6.0, with a p value of <0.027. Smoking correlated with taste disorders, while salivary volume and hypertension had no a correlation with taste disorders. There was correlation between zinc serum levels and zinc intake on taste disorders in the elderly patients. Smoking had a relationship with taste disorders in the elderly patients, whereas salivary volume and hypertension had no correlation with taste disorders in the elderly patients.